Assessment of Mothers’ Knowledge Concerning Child Immunization at the Rural District of Alhawija in Kirkuk Governorate - Ekbal Ghanim (Iraqi National Journal of Nursing Specialties, 2023)
Objective: Identify and describe the scope of knowledge of mothers toward child immunization and its relation to their demographic characteristics and immunization status of their children. Methodology ٨ descriptive study was conducted in (14) villages under the responsibility of (14) primary health care centers (PHCCs), in the rural districts of Alhawija in Kirkuk governorate, from March 24’ال to the end of June 2005. Non probability sample of (200) mothers, who had children aged 12-24 months and (200) children aged 12-24 months. The data were collected by the investigator who interviewed mothers in their houses and filled out the constructed questionnaire formats which designed for the purpose of the study. Internal consistency of reliability determined through the computation of alpha-Chron Bach correlation coefficient for the mother’s knowledge concerning child immunization. Test-retest of reliability was determined through the computation of spearman’s correlation coefficient for child immunization status. The content validity of the constructed questionnaire was determined through the use panel of expens. Data were analyzed through the application of descriptive statistical (frequencies and percentages) and inferential statistical (ChiSquare). Results: The findings revealed that knowledge of mothers toward child immunization were poor, also the decline of the immunization status of children aged 12-24 months. The findings have approved that there is a significant relationship between mothers’ knowledge and demographic variables (age, educational level and occupational status of the children’s parents), characteristics of primary health care center (PHCC) responsible for mothers’ village, the sources of mothers’ knowledge concerning child immunization (physician, health worker, school and mass media) and immunization status of mothers’ children. Recommendations: The study recommended that Ministry of Health would be helpful in impro١ing mothers’ knowledge related to child’s immunization and improve immunization status of children.